PENGARUH BRAND IMAGE DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI PRODUK ERIGO (STUDI PADA GENERASI Z KOTA SEMARANG) - Yessin Laurent Illenia Hidayat; Yoestini Yoestini (Diponegoro Journal of Management, 2023)
ABSTRACT The purpose of this research is to find out and test whether Brand Image and Online Customer Reviews simultaneously influence the purchasing intention of Erigo products. This research was conducted using descriptive and quantitative analysis methods, using questionnaires that had been tested for validity and reliability, statistical analysis using Multiple Linear Regression to measure Brand Image and Online Customer Review factors on their influence on purchasing intention for Erigo products. The results showed that brand image and online customer reviews had a significant positive effect on the intention to purchase Erigo products. This study was dominated by male respondents with an age range of 18-25 years. This study consists of 3 variables with 2 independent variables, namely brand image and online customer reviews, and 1 dependent variable, namely purchasing intention. This study consists of 2 hypotheses, where both hypotheses are accepted.